2010
DOI: 10.1186/1475-2875-9-201
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of socioeconomic factors and their association with malaria in children from the Ashanti Region, Ghana

Abstract: BackgroundThe socioeconomic and sociodemographic situation are important components for the design and assessment of malaria control measures. In malaria endemic areas, however, valid classification of socioeconomic factors is difficult due to the lack of standardized tax and income data. The objective of this study was to quantify household socioeconomic levels using principal component analyses (PCA) to a set of indicator variables and to use a classification scheme for the multivariate analysis of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 18 publications
12
67
1
1
Order By: Relevance
“…This study found that children whose parents/ guardians were into farming and trading were 1.73 and 1.83 times more likely to have a malaria infection. This is in agreement with other reports where those with high socioeconomic status (SES) (OR=0.4, 95% CI: 0.3, 0.5, p<0.001) compared to low SES were associated with lower odds of malaria infection [11]. A parent/ guardian who is a farmer or trader may have lower education and be very busy with activities that bring lower income.…”
Section: Socio-economic and Demographic Risk Factorssupporting
confidence: 83%
See 3 more Smart Citations
“…This study found that children whose parents/ guardians were into farming and trading were 1.73 and 1.83 times more likely to have a malaria infection. This is in agreement with other reports where those with high socioeconomic status (SES) (OR=0.4, 95% CI: 0.3, 0.5, p<0.001) compared to low SES were associated with lower odds of malaria infection [11]. A parent/ guardian who is a farmer or trader may have lower education and be very busy with activities that bring lower income.…”
Section: Socio-economic and Demographic Risk Factorssupporting
confidence: 83%
“…Okebe et al [14] also who found fever in 3% of those infected with malaria and there was increased odds of fever. This is in agreement with studies by Temu et al, in 2012 in Mozambique [11], who found that, children presenting with current fever were infected with malaria (56.7%; 95%CI: 43.7%, 68.9%) compared with those without fever (46.7%; 95%CI: 37.6, 55.9, p=0.037).…”
Section: Fever History Of Fever and Antimalarial Drug Usesupporting
confidence: 82%
See 2 more Smart Citations
“…The questionnaire included a series of questions divided in the following sections: (a) Gender, (b) Age during disability onset in years, (c) Status of multiple disabilities, (d) Status of assistive device availability, (e) Educational status of mother, (f) Reasons for not being enrolled, (g) Household socioeconomic status and (h) School enrollment status of the CwD. We developed household wealth index from nine asset variables using principal component analysis [21,23] as a proxy for household socioeconomic status and classified the score into three categories using terciles.…”
Section: Methodsmentioning
confidence: 99%